2005
DOI: 10.2116/analsci.21.769
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chemical Form of Antimony in Contaminated Soil around a Smelter Using X-ray Absorption Fine Structure

Abstract: Only limited information is available about the behavior of antimony (Sb) in contaminated soils. However, understanding the behavior of Sb in contaminated soils is important, because the toxicity or solubility of this element depends on its chemical state. In this study, we investigated the levels of Sb and the chemical forms of Sb in the soil around a smelter using X-ray absorption fine structure (XAFS) spectra. The highest Sb concentration in the contaminated soil was 2900 mg/kg dry soil. According to Sb-K e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 18 publications
(20 reference statements)
4
25
0
Order By: Relevance
“…The standard reference materials were ground and evenly spread on 3 M tape, whereas the soil samples were pressed into flakes for XANES analysis. The adsorption edge of the XANES was used to distinguish between Sb III and Sb V (Takaoka et al, 2005). Linear combination fitting analysis (LCF) was used to fit a combination of model compounds to unknown spectra using the Athena program in the IFEFFIT package.…”
Section: Analysis Of Sb Speciation Using X-ray Absorption Near Edge Smentioning
confidence: 99%
“…The standard reference materials were ground and evenly spread on 3 M tape, whereas the soil samples were pressed into flakes for XANES analysis. The adsorption edge of the XANES was used to distinguish between Sb III and Sb V (Takaoka et al, 2005). Linear combination fitting analysis (LCF) was used to fit a combination of model compounds to unknown spectra using the Athena program in the IFEFFIT package.…”
Section: Analysis Of Sb Speciation Using X-ray Absorption Near Edge Smentioning
confidence: 99%
“…Data analysis was performed using ATHENA software (Ravel, 2007). The position of the XANES peak was used to distinguish Sb(III) and Sb(V) (Mitsunobu et al, 2006;Scheinost et al, 2006;Takaoka et al, 2005). Linear combination fitting analysis (LCF) was used to fit a combination of model compounds to unknown spectra.…”
Section: X-ray Absorption Near Edge Structure (Xanes) Analysismentioning
confidence: 99%
“…In soil solution Sb is mainly present as pentavalent oxyanion, Sb(OH) 6 À (Filella et al, 2009c;Oorts et al, 2008). This is also the dominant form observed in contaminated soils near smelters and at shooting ranges Takaoka et al, 2005). Methylated Sb species may also play a role in soil depending on biological activity and the bioavailable inorganic Sb pool (Duester et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Only environmental systems containing antimony concentrations high enough for XAS analysis, such as soils around an antimony smelter, [78] affected by an antimony mine pit [79] and from shooting ranges [80] have been studied so far using these techniques. These studies found that antimony was present exclusively as Sb V and that Fe III hydroxide was probably the host phase.…”
Section: Solid Phase Speciationmentioning
confidence: 99%